Not everything is precautionary: towards a typification of different figures in comparative perspective - Valentin, Gabriel (2024)
This article presents and distinguishes measures that were traditionally all located within the precautionary genre, but that in recent years have attempted to be identified with greater precision. The distinction between these measures is relevant, among other reasons because their requirements are not identical, not all of them are admitted in the same cases and the procedure to adopt them must be different, for clearly justified reasons. The topic is approached in an exploratory manner, based on the selection of the Peruvian and Uruguayan systems.